The Effect of Implementation of Patient Orientation Program on Patient's Adaptability - Nur Hidayah; Dardin Dardin; Dian Pratiwi Putri (Journal of Health Science and Prevention, 2019)
New patients undergoing inpatient services at the hospital should be given an orientation program to the care environment. The room orientation program is not only for patients but also for families who will be involved in the treatment process. The purpose of this study was to determine the effect of the implementation of patient orientation program on patient’s adaptability in the internal care room of the Sheikh Yusuf Hospital, Gowa Regency. The design used was pre-experimental in one subject group (one-group pretest and posttest) with the population of all samples obtained by Internal Care at Syekh Yusuf Hospital in Gowa Regency. The sample size was 21 respondents using accidental sampling. The independent variable was the implementation of patient orientation program and the dependent variable was the patient's adaptability. The methodof collecting data was a questionnaire. Data were analyzed using Wilcoxon signed rank test.The result of the study showed that there was an effect of the implementation of the patient orientation program on patient’s adaptability (p = 0,000 Z = -4,059).As the conclusion,if nurses carry out orientation programs to patients according to the procedure, the patient will be able to adapt to the environment and the treatment process.Further research on the effect of implementing an orientation program on patient’s adaptability should be directed to innovative models of patient orientation program.